Termination of Prosecution Based on Restorative Justice as an Expansion of the Meaning of Case Waiver - Effendi, Tolib; Rato, Dominikus; Anggono, Bayu Dwi (RechtIdee, 2024)
The Criminal Procedure Code (KUHAP) and the Attorney General's Act give the public prosecutor and the Attorney General the authority to terminate prosecution, close cases in the interests of the law and set aside cases in the interests of the public. After Prosecutor's Regulation Number 15 of 2020 brings new problems because there is a termination of prosecution based on restorative justice which was previously unknown in both the Criminal Procedure Code and the Attorney General's Act. The purpose of this paper is to determine the position of termination of prosecution based on restorative justice as an extension of the meaning of termination of prosecution,  closing cases in the interests of the law or setting aside cases in the interests of the public, and to determine the legal consequences of termination of cases based on restorative justice. The research method used is doctrinal research to find consistency and legal certainty in the termination of prosecution based on restorative justice.